Mock Encomium between Ibn al-Rumi and Abu al-Tayyib al-Mutanabbi - A. Abed, Prof Dr. Majid (Thi Qar Arts Journal, 2021)
Eulogy and satire are two kinds of Arabic poetry that are independent of each other, and they are known as paradoxical in meaning and construction. Some poets, including Ibn al-Rumi and al-Mutanabbi, were able to combine these two kinds in one poem, employing their genius to produce paradoxical meanings in one poem, in which the burden of interpretation falls on the discerning reader. This research sets out to examine this kind of poetry and the extent to which the term (Mock Encomium or satirical eulogy) might refer to this practice in the poetry of prominent poets such as Ibn Al-Roumi and Al-Mutanabi through analyzing the texts and the discussion of the critics’ opinions related to this type, as well as identifying the reasons and circumstances that contributed to its emergence